1987
DOI: 10.1161/01.hyp.9.6.654
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cations and blood pressure in the People's Republic of China.

Abstract: SUMMARY Blood pressure was measured in the north and in the south of the People's Republic of China in 1002 men and 1006 women. The 24-hour urinary excretion of sodium, potassium, calcium, magnesium, and creatinine was measured, and the relationship between urinary cations and blood pressure was studied. Blood pressure and 24-hour sodium excretion were higher in northern China than in southern China. With some exceptions, a positive correlation was found between urinary sodium and blood pressure and a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
26
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 19 publications
(15 reference statements)
5
26
2
Order By: Relevance
“…This was obtained by weighing all foodstuffs prior to cooking (weighing method). Estimated sodium excretion of 161.9 mmole/day for Japan in the present study is lower than those in Korea (Kesteloot et al 1980), Japan (Ikeda et al 1986), Finland (Karvonen and Punsar 1977), Heidelberg (Schlierf et al 1980), China (Kesteloot et al 1987), and Japan in the Intersalt study (1988), and is higher than those in the U.S.A. (Watson et al 1980;McCarron et al 1984;Gruchow et al 1985), Belgium (Staessen et al 1981), and the Netherlands (Kok et al 1986). Potassium of 56.2 mmole/day in the present study is comparatively lower than in the Netherlands (Kok et al 1986) and Japan (Ikeda et al 1986), higher than in China (Kesteloot et al 1987) and Japan in the Intersalt study (1988), and is close to Korea (Kesteloot et al 1980) and western countries (Staessen et al 1981;McCarron et al 1984 ;Gruchow et al 1985).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This was obtained by weighing all foodstuffs prior to cooking (weighing method). Estimated sodium excretion of 161.9 mmole/day for Japan in the present study is lower than those in Korea (Kesteloot et al 1980), Japan (Ikeda et al 1986), Finland (Karvonen and Punsar 1977), Heidelberg (Schlierf et al 1980), China (Kesteloot et al 1987), and Japan in the Intersalt study (1988), and is higher than those in the U.S.A. (Watson et al 1980;McCarron et al 1984;Gruchow et al 1985), Belgium (Staessen et al 1981), and the Netherlands (Kok et al 1986). Potassium of 56.2 mmole/day in the present study is comparatively lower than in the Netherlands (Kok et al 1986) and Japan (Ikeda et al 1986), higher than in China (Kesteloot et al 1987) and Japan in the Intersalt study (1988), and is close to Korea (Kesteloot et al 1980) and western countries (Staessen et al 1981;McCarron et al 1984 ;Gruchow et al 1985).…”
Section: Discussioncontrasting
confidence: 48%
“…; Kok et al 1986), whereas, in Oriental population studies, sodium intake correlated positively with blood pressure (Kesteloot et al 1980(Kesteloot et al , 1987.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The 24 h urine collection quantifying sodium excretion is the accepted method in Diet, blood pressure and osteoporosis J Woo et al many epidemiological studies examining the relationship between salt intake and blood pressure. 25,26 However, collection of 24 h urine in elderly people is more prone to inaccuracies as the procedure is dependent on adequate manual dexterity and cognitive function. The volume collected tends to be less than the true 24 h urine output.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary and urinary sodium, urinary sodium-to-potassium ratio were significantly and positively correlated with BP, dietary and urinary potassium were inversely related to BP. 8,13,16,[20][21][22][23] Some Chinese investigations have indicated that average BP, dietary and urinary sodium, and urinary sodium-to-potassium ratio were consistently higher in the north than in the south of China, [2][3]23 and dietary sodium-to-potassium ratio was positively correlated with BP. 24,25 In the analysis of this study, we noticed an association between dietary variables and different BP patterns.…”
Section: Discussionmentioning
confidence: 99%